2015
DOI: 10.1097/bco.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Two admission pathways for elderly patients with hip fracture

Abstract: Background:The incidence of hip fractures increases exponentially after the age of 65, and that number will continue to rise over the coming decades as the population ages. In an attempt to provide better patient care for elderly patients with hip fractures and multiple co-morbidities, some centers have created various forms of shared-responsibility services, multidisciplinary care teams, or hospitalist models of care for these patients. The purpose of this study was to examine the clinical outcomes of two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“… 37 Two studies reported no association between clinical pathway and time to surgery after hip fracture. 42 43 We identified nine factors with proposed mechanisms underlying the association between system factors and timing of surgery after hip fracture ( table 3 , figure 2 ). Resource availability was the proposed mechanism for the association between out-of-hours admission, 28 32 medical test, 22 prioritisation, 22 surgery type, 34 insurance status 30 and hospital type and region 30 with time to surgery after hip fracture.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Two studies reported no association between clinical pathway and time to surgery after hip fracture. 42 43 We identified nine factors with proposed mechanisms underlying the association between system factors and timing of surgery after hip fracture ( table 3 , figure 2 ). Resource availability was the proposed mechanism for the association between out-of-hours admission, 28 32 medical test, 22 prioritisation, 22 surgery type, 34 insurance status 30 and hospital type and region 30 with time to surgery after hip fracture.…”
Section: Resultsmentioning
confidence: 99%
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS and 20 programs did not. Delayed TTS cutoffs were most often defined dichotomously as more than 24 hours, more than 36 hours, more than 48 hours, or more than 72 hours, although some studies collected continuous data.…”
Section: Resultsmentioning
confidence: 90%
“…[10][11][12] To address delays in TTS, diverse strategies, including targeted resource management, [13][14][15] comanagement programs between orthopedics and medicine or geriatrics, [16][17][18][19] documented protocols, 20,21 and financial incentives, [22][23][24] have been implemented with varying levels of success. 17,19,[25][26][27][28] Challenges in implementing evidence-based improvement interventions include organizational knowledge, medical socialization (ie, medical decision-making based on knowledge from trusted peers or mentors rather than directly from peer-reviewed evidence), and patient and surgeon factors, among others. 29,30 To be successful, evidence-based improvement interventions should be tailored to the context in which they will be implemented; however, there is currently no nationallevel guidance for how hospitals can improve TTS based on their own context.…”
Section: Introductionmentioning
confidence: 99%
“…Facility-level factors, including larger hospital size, annual surgical volume, and a medical optimization protocol, have also been associated with delays . To address delays in TTS, diverse strategies, including targeted resource management, comanagement programs between orthopedics and medicine or geriatrics, documented protocols, and financial incentives, have been implemented with varying levels of success …”
Section: Introductionmentioning
confidence: 99%